Spectroscopic Diagnostic of Laser-Induced Zn Plasma - Magid, Hayim Chasib; Waleed Jabbar Mhana; Hanaa Salih Sabaa (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The sample’s physical characteristics and laser parameters impact the generation and characterization of Laser-Induced Plasma (LIP), which is a relevant phenomenon in many applications. We investigated the effect of laser energy on laser-induced Zn plasma characterization in this study. A Zn plasma with a repeating frequency of 6 Hz, a first wavelength of 1064 nm, a pulse duration of 10 ns, and a laser energy range of 300 mJ to 500 mJ was created using a Q-switched ND: YAG laser. The basic plasma properties, such as electron temperature and density, were estimated using optical emission spectroscopy (OES). The electrons’ temperature was measured by the Boltzmann plot method, and the value of the electrons’ temperature ranged from 1.6 eV to 2.051 eV in the laser energy range (300-500) mJ. In electron density estimation using the Stark broadening methods, the density value range from 12.75×1017 cm-3 to 19.50×1017 cm-3, in laser energy range (300-500 ) mJ. In addition, various plasma characteristics such as plasma frequency (fp), the number of particles in the Debye sphere (ND), and Debye length (λD) were estimated. We found that laser energy affects every plasma parameter.